Pediatric Dysphonia - A Review - Swain, Santosh Kumar; Nahak, Bulu; Sahoo, Loknath; Munjal, Sampada; Sahu, Mahesh Chandra (Indian Journal of Child Health, 2019)
Dysphonia or hoarseness of voice is defined as a disorder characterized by altered voice quality, loudness, pitch, or vocal effort which impairs the communication or hamper voice-related quality of life. Dysphonia or hoarseness of the voice is a commonly encountered vocal symptom among children. The etiological profiles of dysphonia among children are variable. The laryngoscopic examination is required for identification of the lesions. Pediatric dysphonia is a common cause for referral to pediatric otolaryngologists and management sometimes vary. Voice disorders in children are often due to strenuous speaking, screaming, singing, excess coughing, and habit of clearing throat. Endoscopic and physical examinations are the key behind the assessing dysphonic child. Flexible nasopharyngolaryngoscopy is suitable for accurate diagnosis. Additional examinations are sometimes needed during the assessment. There several treatment options for pediatric dysphonia and often based on the etiology.